Patient selection for subcutaneous versus sublingual immunotherapy. Issue 6 (December 2015) - Unknown
Abstract : Purpose of review: With the Food and Drug Administration's approval of sublingual allergen-specific immunotherapy (SL-AIT) tablets for grass and ragweed pollen, SL-AIT is progressively gathering importance not only in Europe, but also in the United States and other parts of the world. We reviewed issues related to the selection of patients for the sublingual or the subcutaneous route for allergic patients, based on what has been published since January 2014 on subcutaneous-versus-SL-AIT efficacy, safety and other issues. Recent findings: As patient's adherence seems one of the major problems in real-life AIT, investigators have sought how to enhance AIT simplicity by changing the route to home-administrated SL-AIT, and by shortening the subcutaneous-allergen-specific immunotherapy (SC-AIT) build-up or maintenance phase. The latter was safe with several hypoallergenic extracts. As for SL-AIT, double blind placebo-controlled large trials in patients with allergic rhinitis and asthma have shown the efficacy and safety of ragweed pollen and house dust mite SLIT tablets and highly concentrated liquid formulations, primarily in adults. A large trial with SLIT in 3-year-old children was effective. Summary: With the improvement of SL-AIT efficacy, the selection of SC-versus-SL-AIT will probably increasingly be based not on efficacy, but on practical aspects, without losing sight of which SL-AIT products have proven efficacy.